EFFECT OF COMPETITION ON THE INTERACTION BETWEEN MAIZE AND WEED EXPOSED TO WATER DEFICIENCY - Freitas, Cláudia Daianny Melo (2019)
The ability of plants to adapt to water deficient conditions in soil is directly related to the competitive ability of each species. The objective of the present study was to evaluate the effects of water deficiency and interspecific competition on the growth components of maize (Zea mays), brachiaria (Urochloa decumbens), and hairy beggarticks (Bidens pilosa L). The experimental design was in randomized blocks, with eight replications. The treatments were arranged in a 5 × 2 factorial design, with the first factor corresponding to the different competitive arrangements among species (maize + U. decumbens, maize + B. pilosa, maize without competition, U. decumbens without competition, and B. pilosa without competition). The second factor constituted two water regimes (daily irrigation and water deficit). The soil water deficient condition strongly decreased maize plant growth; however, it had little or no effect on the growth of weeds U. decumbens and B. pilosa. Interspecific competition decreased the growth of maize plants and U. decumbens, and intensified the negative effects of water deficiency on these species. Interspecific competition and water deficiency also decreased the N, P, and K content in maize plants, which contributed to the effects on plant growth. U. decumbens was more competitive with maize compared to B. pilosa.